Sertifikasi Produk Halal dalam Perspektif Mashlahah Mursalah - Eka Rahayuningsih; M. Lathoif Ghozali (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine the certification of halal products through the LPPOM MUI. In an effort to maintain the sustainability and effectiveness of halal certification and smooth administration, LPPOM MUI makes provisions for the halal guarantee system through its letter No: SK 13 / Dir / LPPOM MUI / III / 13 dated March 31, 2013. This halal product certification system is an integrated system that neatly arranged and maintained properly to regulate the ingredients in the product, human resources involved in the production, production process, and product distribution procedures. In responding to the needs of the community and the responsibility of the MUI (Indonesian Ulama Council) to protect the community, efforts are made to establish an institute for the study of drugs, food, cosmetics. In this case the researcher is interested in revealing that with the existence of this halal product certification, whether it has made it easy for all people to maintain their religion and assets or make it difficult for people to choose products that must be consumed for daily life. Humans will get happiness when all needs both dhohir and heart, and all desires are fulfilled. This study uses qualitative research with a phenomenological and normative approach. Data retrieval used is secondary data sourced from publications which include scientific journals, books, websites and newspapers that make this problem discussed in research.